INFLUENCE OF MORPHOLOGY ON PHONEME IDENTIFICATION IN SPOKEN CROATIAN - Erdeljac, Vlasta (Array, 1999)
The representation of the morphological structures in the mental lexicon recently constitutes the inevitable topic in the investigation of cognitive language data processing. In the present paper within the framework of the spoken word recognition the influence of the noun case functions on the phoneme identification in Croatian is investigated. By means of the gate-paradigm 36 subjects listened to and identified 24 words. The results showed strong influence of the morphological component, especially of nominative case, on the word recognizability regardless the suffix phoneme (/a/ for feminine and /e/ for neuter nouns. The results also showed the dynamics of the auditive word identification processing and the decision-bias point position. The results could be interpreted in terms of decompositional storage of morphological information of regular complex words in mental lexicon.